Launching, maintaining, expanding and disseminating crowd-sourced information in drylands: KAZNET manual - Lepariyo, Watson; Shikuku, Kelvin Mashisia; Baraza, Meshack; Galgallo, Diba; Gobu, Wako; Godana, Nura; Banerjee, Rupsha R. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
KAZNET (kazi kwa net), translated from Kiswahili to mean “working within a network”, is an information crowdsourcing initiative and a decision support tool designed with the goal to address climate and non-climate shocks by informing resilience programming, targeted intervention, early warning, and early action. To achieve this goal, KAZNET facilitates the dynamic monitoring of multidimensional indicators of shocks and resilience indicators through the collection and dissemination of near-real-time information about livestock markets, forage conditions, household food and nutrition security in livestock production systems, particularly in the drylands. This document is an update to the initial set up manual by Chelanga et al. (2022), accessible at https://hdl.handle.net/10568/130313, providing a detailed guide to setting up and maintaining sentinel zones in the horn of Africa. Specifically, this updated guide provides details of adjustments made to the sentinel zones approach in terms of setting up, software development, and real-time dissemination of the information to communities and other national stakeholders to support decision making and resilience programming.